THE GOOD MOTHER AS REPUTATIONAL PERFORMANCE: MYTH AND SOCIAL SURVEILLANCE IN LEFT-HANDED GIRL (2025) - Ni Luh Ayu Sukmawati; Wen-Hung Chao; Denny Antyo Hartanto; Bambang Aris Kartika (Institut Seni Indonesia Yogyakarta, 2026)
This article examines Left Handed Girl (2025) to refine how patriarchy works through moralised of reputation and public evaluation. Patriarchy appears as a social process sustained through gendered self policing, where mothers protect family face by managing secrecy, shame, and communal judgement. The framework draws on Roland Barthes’ semiotics of denotation, connotation, and myth, Friedrich Nietzsche’s moral genealogy of ressentiment, bad conscience, and the conversion of debt into guilt, and Judith Butler’s performativity as repeated acts shaped by social norms. The study uses close readings of selected sequences and recurring motifs that organise the film’s moral economy. Motifs include the stigmatisation of left handedness as the devil’s hand, the night market as a semiotic economy of female commodification, the concealment of nonmarital motherhood, and an incident where a pet’s fatal fall is disavowed to avert censure. Barthesian myth shows how reputational discipline becomes common sense, Nietzschean genealogy explains how external judgement turns inward as bad conscience, and Butlerian performativity frames concealment as affective labour that produces the figure of the good mother. The findings portray patriarchy as reproduced through women’s enforced moral responsibility, binding care to coercive respectability